2005
DOI: 10.1038/sj.bmt.1704827
|View full text |Cite
|
Sign up to set email alerts
|

Circulating dendritic cell subset levels after allogeneic stem cell transplantation in children correlate with time post transplant and severity of acute graft-versus-host disease

Abstract: Summary:We examined the recovery of circulating monocytoid (Lin À CD11 þ HLA À DR þ ) and plasmacytoid (Lin À CD123 þ HLA À DR þ ) precursor (pre) dendritic cell (DC) subsets after allogeneic stem cell transplantation (SCT) in 39 children, using age-matched healthy children as controls. The frequencies of DCs in peripheral blood samples were determined by flow cytometry. The initial recovery of DC occurred simultaneously with myeloid engraftment. However, with time, DC subset values declined, being very low 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 34 publications
1
27
1
Order By: Relevance
“…Similar to our findings, Reddy et al 26 recently showed, in a series of patients treated with conventional myeloablative allo-SCT, that the reconstitution of absolute numbers of circulating DC was an independent predictor of post-transplantation survival and relapse. Interestingly, these and other authors 27,28 also found a correlation between DC counts and acute GVHD, unlike in our series in which high DC counts were associated with a lower relapse rate without an increased incidence of acute GVHD. This dissociated relation of DC numbers with the graft-versus-leukemia effect and GVHD was also found by Sato et al, 29 who demonstrated that regulatory DC administered after allogeneic transplantation in mice protected against both relapse and acute GVHD.…”
Section: Discussioncontrasting
confidence: 52%
“…Similar to our findings, Reddy et al 26 recently showed, in a series of patients treated with conventional myeloablative allo-SCT, that the reconstitution of absolute numbers of circulating DC was an independent predictor of post-transplantation survival and relapse. Interestingly, these and other authors 27,28 also found a correlation between DC counts and acute GVHD, unlike in our series in which high DC counts were associated with a lower relapse rate without an increased incidence of acute GVHD. This dissociated relation of DC numbers with the graft-versus-leukemia effect and GVHD was also found by Sato et al, 29 who demonstrated that regulatory DC administered after allogeneic transplantation in mice protected against both relapse and acute GVHD.…”
Section: Discussioncontrasting
confidence: 52%
“…Our result that lower pDC count early post-SCT is associated with moderate to severe aGVHD was also found by previous studies. [13][14][15][16]37 This may be due to a delayed recovery of DCs for both aGVHD and cGVHD with the pDC subset being more affected. 13,15,16,18,19,38 The reasons for lowered DC counts in PB may be complex as lowered counts were previously identified in individuals diagnosed with allergic diseases, autoimmune diseases or malignant diseases.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, return to normal levels takes 1 year for mDCs and longer for pDCs. 13,14 Previous publications found lower pDC 15 or both lower mDC and pDC 13,14,16 counts in the PB of patients with moderate to severe acute GVHD (aGVHD). However, others found no connection to aGVHD 17 or higher measurements in an early phase of aGVHD.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies in children receiving myeloablative conditioning have associated DC recovery with severe acute GVHD. 10,11 In an adult setting with RIC, low DC recovery has been associated with a higher probability of treatment-related mortality. 12 In this study, we prospectively performed a detailed analysis of immune reconstitution in MUD and HP HSCT with CD3/CD19-depleted grafts in 30 pediatric patients to identify specific cells that may mediate an early GVL effect.…”
Section: Introductionmentioning
confidence: 99%